Appearing moderate or radical? Radical left party success and the two-dimensional political space - Werner Krause (West European Politics, 2020)
Challenger parties' electoral successes have attracted increasing scholarly attention. Based on the example of West European radical left parties, this article investigates whether and how centripetal and centrifugal positional movements on different conflict dimensions influence the election results of these parties. Depending on parties' issue-linkages, these strategies will have a different effect for the economic and the non-economic issue dimension. Due to radical left parties' long-term commitment and a strong party-issue linkage on economic issues, more moderate positions will play to their electoral advantage. In contrast, far-left parties compete with social democratic and green-libertarian parties for party-issue linkages on the non-economic issue dimension. Here, they benefit from promoting centrifugal strategies. Based on time-series cross-section analyses for 25 West European far-left parties between 1990 and 2017, the empirical results show that the success of radical left parties' positional strategies varies with the conflict dimension in question and that this effect is only partly moderated by the positions of competing mainstream left parties.
doi:10.6084/m9.figshare.10248824.v1
Keywords: 330; radical left parties; party competition; electoral behaviour; elections; political parties